Importance of species translocations under rapid climate change - Nathalie Butt; Alienor L.M. Chauvenet; Vanessa M. Adams; Maria Beger; Rachael V. Gallagher; Danielle F. Shanahan; Michelle Ward; James E.M. Watson; Hugh P. Possingham (Conservation Biology, 2021)
Species that cannot adapt or keep pace with a changing climate are likely to need human intervention to shift to more suitable climates. While hundreds of articles mention using translocation as a climate‐change adaptation tool, in practice, assisted migration as a conservation action remains rare, especially for animals. This is likely due to concern over introducing species to places where they may become invasive. However, there are other barriers to consider, such as time‐frame mismatch, sociopolitical, knowledge and uncertainty barriers to conservationists adopting assisted migration as a go‐to strategy. We recommend the following to advance assisted migration as a conservation tool: attempt assisted migrations at small scales, translocate species with little invasion risk, adopt robust monitoring protocols that trigger an active response, and promote political and public support.